2006
DOI: 10.1111/j.1469-8986.2006.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Masked repetition priming and event‐related brain potentials: A new approach for tracking the time‐course of object perception

Abstract: This study reports a new approach to studying the time-course of the perceptual processing of objects by combining for the first time the masked repetition priming technique with the recording of eventrelated potentials (ERPs). In a semantic categorization task ERPs were recorded to repeated and unrelated target pictures of common objects that were immediately preceded by briefly presented pattern masked prime objects. Three sequential ERP effects were found between 100 and 650 ms post-target onset. These effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
124
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 25 publications
23
124
3
1
Order By: Relevance
“…Thus the N300 probably refl ects early semantic categorization of an object, which occurs prior to the determination of more specifi c identity information. Eddy et al 17 also state that the anterior negativity (N300) refl ects processing of object-specifi c representations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the N300 probably refl ects early semantic categorization of an object, which occurs prior to the determination of more specifi c identity information. Eddy et al 17 also state that the anterior negativity (N300) refl ects processing of object-specifi c representations.…”
Section: Discussionmentioning
confidence: 99%
“…This component took the form of a larger negativity to target words that were unrelated to their preceding prime words (e.g., phone-truck), intermediate for targets that overlapped with primes in all but one letter position (e.g., trock-k k truck), and smallest for complete repetitions (e.g., truck-k k truck). Grainger and Holcomb (in press) have argued that such N250 effects, which were not seen for individual letters (Petit et al, 2006) or objects (Eddy et al, 2006), reflect the process whereby prelexical orthographic representations (letters and letter clusters) are mapped onto whole-word orthographic representations.…”
mentioning
confidence: 99%
“…These repetition effects post-400 ms are qualitatively different to the N1 and N250, and have been associated with conceptual processing for example by Henson et al (2004) who observed repetition effects between (400-500 ms) elicited by attended objects, and Eddy et al (2006) who observed repetition effects between (350-650 ms) elicited by masked primes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some debate as to what degree visual masking renders a stimulus 'unattended' (Henson, 2003) rather than just harder to see. In addition, the study of Eddy et al (2006) presented prime and probe stimulus (even if temporally separated) in the same location and this type of manipulation may not fully prevent the prime from being attended as the task does not involve the necessity for an attentional shift (cf. Wolfe, 2000; Experiment 1 of Lachter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation